Switch/sucrose‐non‐fermentable (SWI/SNF) complex (SMARCA4, SMARCA2, INI1/SMARCB1)‐deficient colorectal carcinomas are strongly associated with microsatellite instability: an incidence study in 4508 colorectal carcinomas. Issue 6 (24th February 2022) - Ahadi, Mahsa S; Fuchs, Talia L; Clarkson, Adele; Sheen, Amy; Sioson, Loretta; Chou, Angela; Gill, Anthony J
Abstract : Aims: Loss of expression of mammalian switch/sucrose‐non‐fermentable (SWI/SNF) [BRG1/BRM‐associated factor (BAF)] complex subunits, including SMARCA4, SMARCA2 and INI1/SMARCB1 (termed SWI/SNF complex deficiency), has been reported in colorectal carcinomas (CRCs) but its frequency and clinical significance are uncertain. Methods and results: We performed immunohistochemistry for SMARCA4, SMARCA2 and SMARCB1 on 4508 consecutive resected CRCs. Loss of SMARCA4 expression was found in 13 cases (0.3%), loss of SMARCA2 expression was found in 59 cases (1.3%), and loss of SMARCB1 expression was found in 21 cases (0.4%). Some CRCs showed loss of expression of more than one subunit, so that 84 CRCs (1.7%) were deficient for at least one component. SWI/SNF complex deficiency was associated with higher grade, a right‐sided location, mismatch repair deficiency, and BRAF V600E mutation ( P < 0.05); 5.8% of mismatch repair‐deficient (MMRd) cases and 5.4% of BRAF V600E‐mutant cases were SWI/SNF complex‐deficient, as compared with 0.9% and 0.4% of mismatch repair‐proficient and BRAF‐wild‐type cases ( P < 0.001). Any loss of SMARCB1 expression and global loss of SMARCA2 expression were associated with statistically significant worse overall survival, whereas SMARCA4‐deficient cases showed a trend only towards poor overall survival ( P = 0.121). In multivariate analysis, any loss of SMARCA4 expression and global loss of SMARCA2 expression were associated with worse survival [odds ratio (OR) 3.33, P = 0.019; and OR 3.39, P < 0.001]. Of particular note, among the subgroup of cases that were MMRd and BRAF V600E‐mutated (otherwise considered to be a good prognostic group), loss of SMARCA4 expression was associated with much worse median survival (10.5 months versus 110.9 months; P = 0.003). Conclusions: SWI/SNF complex deficiency is rare in CRC but is enriched in MMRd cases. Identifying these cases has morphological associations and prognostic significance, and in the future may have potential therapeutic implications. Abstract :